USING TRANSACTIONAL STRATEGIES INSTRUCTION IN TEACHING READING DESCRIPTIVE TEXT OF SMAN 1 SEGEDONG - Oktari, Hesti; Arifin, Zainal; Arifin, Eusabinus (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
Abstract: The purposes of this research are to find out whether Transactional Strategies Instruction is effective or not in teaching reading comprehension of descriptive text and to find out the effectiveness of using Transactional Strategies Instruction in teaching reading comprehension of descriptive text. The research applies pre-experimental study with one group of pre-test and post-test. The population of this research is tenth grade students of SMAN 1 Segedong. The sample are 30 students of class XC. Based on the research findings, the t-test is 13.6 where the degree of freedom is 2.045. It can be seen that the t-test is higher than the t-table. Therefore, the null hypothesis (Ho) is rejected and the alternative hypothesis (Ha) is accepted. The effect size (ES) of treatment is 2.31. Based on the category, the Effect Size (ES) is higher than the category (2.31>1.00) and categorized as strong effect. Therefore, it can be concluded that using Transactional Strategies Instruction in teaching reading comprehension of descriptive text to the tenth grade students of SMAN 1 Segedong in academic year 2016/2017 is effective and strong effect. Key Word : Reading Comprehension, Transactional Strategies Instruction, Descriptive Text